Explaining Tonality : Schenkerian Theory and Beyond - Brown, Matthew, 1957- (Book collections on Project MUSE., 2005)
"Along the way, the book explores six methodological criteria that help in building, testing, and evaluating a plausible theory of tonality or, indeed, any other musical phenomenon: accuracy, scope, fruitfulness, consistency, simplicity, and coherence. It reveals how understanding the tonality of a piece can shed light on other aspects of musical composition. And, in conclusion, it describes some ways in which Schenkerian theory might fruitfully develop in the future."--Jacket